2017
DOI: 10.1007/s11356-017-9528-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo formation of dioxins from milled model fly ash

Abstract: Municipal solid waste incineration (MSWI) fly ash has been classified as hazardous waste and needs treatment in an environmentally safe manner. Mechanochemical (MC) treatment is such a detoxification method, since it destroys dioxins and solidifies heavy metals. Milling, however, also introduces supplemental metals (Fe, Ni, Cr, Mn…), following wear of both steel balls and housing. Milling moreover reduces the particle size of fly ash and disperses catalytic metal, potentially rising the reactivity of fly ash t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Numerous halogenated compounds, including dioxins and furans successfully are destroyed (Cagnetta et al, 2016, Mubeen et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous halogenated compounds, including dioxins and furans successfully are destroyed (Cagnetta et al, 2016, Mubeen et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, WIFA, despite initially harboring a higher PCDD/F content, exhibited a remarkable degradation effect after LTTD treatment under identical conditions (400 °C, 1 h, 1% O 2 ). This highlights the efficacy of predechlorination strategies aimed at reducing Cl sources and catalytic metals in inhibiting the regeneration of PCDD/F. , …”
Section: Resultsmentioning
confidence: 94%
“…This highlights the efficacy of predechlorination strategies aimed at reducing Cl sources and catalytic metals in inhibiting the regeneration of PCDD/F. 40,41 Further analysis in Figures S5 and S6 delves into the distribution of the congener concentration and toxicity of PCDD/Fs before and after predechlorination. It was observed that both IFA and WIFA had the highest OCDD content, accounting for 42.7 and 43.8%, respectively, followed by 1,2,3,4,6,7,8-HpCDD at 15.7 and 14.8%, respectively.…”
Section: Pcdd/f Distribution In Predechlorinated Ifa (Wifa) Treated W...mentioning
confidence: 94%
“…The presence of elements, notably; chlorine, oxygen, and copper is necessary for PCDD/F formation in the De novo synthesis, but contribution of combustion gasses such as CO or CO 2 in the formation of polychlorinated dibenzofuran (PCDF) by this mechanism is remarkably insignificant [1]. Besides the concentration of oxygen, the activity of fly ash also controls the rates of formation of PCDD/F, therefore, since the chlorine in this dioxin synthetic pathway originates from the chloride salt of a transition metal ordinarily found at the surface of fly ash, the contribution of the concentration of chlorine in the combustion gaseous mixture is insignificant [71]. The numerous products generated from the De novo synthesis are in the following order of prominence CBz > CP > PCDFs > PCDDs > dl − PCB [41,83,134].…”
Section: The De Novo Synthesis Of Dioxins and Furansmentioning
confidence: 99%
“…Polychlorinated benzenes are suggested to form by either radical mechanisms or by the combination of chlorine and chlorobenzyl radicals [127]. Eventually, the addition of two chlorobenzyl radicals gives rise to polychlorinated biphenyls, PCBs, which are possible precursors for the formation of PCDFs [71,131]. The De novo mechanism suggests that there are structures similar to the dibenzo-p-dioxins and dibenzofurans in the residual carbon attached to the fly ash [127].…”
Section: The Precursor Synthesis Of Dioxins and Furansmentioning
confidence: 99%